FIGURATIVE LANGUAGE ENTRY-LEVEL ANALYSIS ON ROBERT FROST’S A MINOR BIRD - Gabriel Chamelia Sudibyo (TONIL: Jurnal Kajian Sastra, Teater dan Sinema, 2019)
Abstract: Poem employs a variety of aesthetic devices varying from rhythm, meter, and on textual literary content: figurative language. Through the usage of figurative language, a short poem is capable to deliver more in-depth meaning in each word. In the poem A Minor Bird by Robert Frost, the poet employs symbols and imagery as the most prominent figurative language device. Hence this paper aims to identify these devices and further explains it as a poem breakdown analysis in hope to enlighten readers’ perception and understanding against entry-level poem analysis. The method used in this research is library research and literature review. Key words: Robert Frost, figurative language, poem analysis